Effects of acute and chronic handling stress on antiviral responses in Atlantic salmon (Salmo salar) red blood cells and testing of stress target genes - Aardal, Martine (UiT The Arctic University of Norway, 2023)
The salmonids in today’s Norwegian aquaculture are exposed to many stressors, like suboptimal water quality, crowding and handling. This project focuses on red blood cell (RBCs) function in Atlantic salmon and how cellular responses are affected by stress. Since fish RBCs are nucleated and can change their gene expression, one of the main goals of this thesis is to better understand how the RBCs function in the fight against viruses after the fish have been exposed to handling stress. Lastly, one also wants to find a better way to monitor stress levels in Atlantic salmon RBCs by testing and finding stress biomarkers. A small in vivo stress trial was run, where Atlantic salmon were exposed to acute and chronic handling stress. There were no long-lasting significant changes in stress hormones, haemoglobin levels, or antiviral responses to poly (I:C) in the RBCs when measured after 1 and 4 days. However, the acute stress group had a trend towards higher blood plasma cortisol level and the RBCs had a lower antiviral response to poly (I:C) than samples with lower blood plasma cortisol. Because of the unconclusive in vivo results, ex vivo trials with cultures of Atlantic salmon RBCs were run to try and find more stable stress biomarkers. Stimulation with the chronic stress hormone hydrocortisone showed an upregulation in gene expression of FkBP prolyl isomerase 1 (FkBP1). For the in vivo stress trial samples, the gene expression of FkBP1 was not upregulated in the RBCs for the stress groups, probably due to the low hormone levels upon sampling. Cultures of Atlantic salmon RBCs were also stimulated with isoproterenol and epinephrine in hope of finding acute stress biomarkers. There was a significant increase in gene expression of carbonic anhydrase 1 (Cahz) in response to isoproterenol, and heat-shock protein (HSP)90aa in response to epinephrine. In this ex vivo trial, Atlantic salmon RBCs were also stimulated with poly (I:C) to test the effects of stress hormones on antiviral responses. The response to poly (I:C) on ...